Kinerja kelembagaan program sanitasi lingkungan berbasis masyarakat (SLBM) - Denok Kurniasih; Paulus Israwan Setyoko; M Imron (Faculty of Social and Political Science, Universitas Airlangga, 2016)
SLBM Program implementation in Banyumas Regency involves many stakeholders, one of them is community. Through KSM, community has authority to manage program from, beside government roles as facilitator. Thus, institutional system is required to support performance of KSM. By using descriptive qualitative approach, this research aimed to analyze institutional performances of KSM and aspects which is able to support and inhibit the institutional performance of KSM. This research found that institutional performance of KSM has not been able to reach policy goals. This can be seen from community participation in SLBM program. Program’s effectiveness is also not optimal. Thus, there have been no changes in the community habits of sanitation-related issues. Moreover, some of support and inhibit aspects of institutional performance of KSM has indentified.